Investigating the association between germ line specification and sequence evolution in vertebrates - Evans, Teri (2015)
Within vertebrates the primordial germ cells (PGCs) can either be induced by embryonic signals (known as epigenesis), or predetermined by maternally deposited germ plasm (preformation). Epigenesis is known to be the ancestral mechanism, while preformation has evolved multiple times. Epigenesis has been proposed to enforce a developmental constraint on the evolution of somatic structures that is released in species which acquired preformation. In accordance with this hypothesis, the mesoderm gene regulatory network is conserved between urodeles and mammals, which have retained epigenesis, but has diverged in anurans (preformation). An increase in speciation has also been shown in vertebrates which have acquired preformation. Our aims were to investigate whether the mode of PGC specification associates with the molecular evolution of protein-coding genes. We downloaded all publicly available vertebrate sequences. These were combined with our three novel transcriptomes from axolotl, sturgeon and lungfish. In line with previous analyses, we built 4-taxon trees to investigate the extent of phylogenetic incongruence. This revealed a bias associated with the mode of PGC specification, caused by a significant difference in the rate of evolution. Many genes in species that have acquired preformation are evolving significantly faster than in their sister taxa undergoing epigenesis. These sequences are typically expressed in early development, and are ancient genes with known orthologs at the base of Eukaryotes. Additionally, we show that Oct4 and Nanog, which are crucial for pluripotency, have been lost in taxa using preformation. Therefore our results are consistent with the proposal that developmental constraint, imposed by epigenesis, is released in species undergoing preformation.